The Parkland Mass Shooting and the Path to Intended Violence: A Case Study of Missed Opportunities and Avenues for Future Prevention - Schildkraut, Jaclyn (Homicide studies, 2024)
The 2018 mass shooting at Marjory Stoneman Douglas High School in Parkland, Florida reignited a discourse about safety and prevention that often follows such tragedies. Using a case study approach, we analyze the events leading up to the shooting (via official records from law enforcement and the shooting’s review commission) to identify missed opportunities for intervention, de-escalation, and ultimately prevention. The Path to Intended Violence model is employed to highlight the perpetrator’s escalating behaviors from grievance through the attack itself. The lessons learned then are utilized to offer recommendations for schools and communities seeking to prevent similar mass violence attacks.